2019
DOI: 10.1037/dev0000626
|View full text |Cite
|
Sign up to set email alerts
|

Measuring early learning and development across cultures: Invariance of the IDELA across five countries.

Abstract: Save the Children, Washington, DCRelatively little research has addressed whether conceptual frameworks of early learning generalize across different national contexts. This article reports on a cross-country measurement invariance analysis of the International Development and Early Learning Assessment (IDELA). The IDELA is a direct assessment tool for 3-to 6-year-old children, intended to measure Early Literacy, Early Numeracy, Motor, and Social-Emotional development. Its generalizability is evaluated using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Wolf et al (2017) found strong support for a four-factor model (including items measuring motor skills but not EF), compared to other alternative factor structures in Ethiopia. A follow-up study replicated the factor structure in four additional low-and middle-income countries and found evidence of partial measurement invariance for each domain across the four countries (Halpin et al, 2019). Accordingly, in this study we operationalize each domain-numeracy, literacy, EF, and SE-as a unidimensional construct.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…Wolf et al (2017) found strong support for a four-factor model (including items measuring motor skills but not EF), compared to other alternative factor structures in Ethiopia. A follow-up study replicated the factor structure in four additional low-and middle-income countries and found evidence of partial measurement invariance for each domain across the four countries (Halpin et al, 2019). Accordingly, in this study we operationalize each domain-numeracy, literacy, EF, and SE-as a unidimensional construct.…”
Section: Methodsmentioning
confidence: 73%
“…The tool used to measure SE in this study-the IDELA-was designed for global use, yet is grounded in Western constructs of social and emotional skills (Pisani et al, 2018). Although the IDELA has been found to demonstrate measurement invariance across five diverse countries in three regions (Halpin et al, 2019), it does not necessarily capture the full range of social and emotional competencies that may be important for school success in the Ghanaian cultural context. A measure that specifically operationalizes children's competence in interpersonal relationships within the Ghanaian classroom context may identify skills necessary for learning that are not captured by IDELA.…”
Section: Links Between Early Ef and Se And Later Academic Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…See Pisani et al () for details on the development of the IDELA items. Recent studies have assessed the psychometric properties and factor structure of the IDELA (Wolf et al, ), as well as the measurement invariance of the factors across five countries (Halpin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…SeePisani et al (2018) for details on the development of the IDELA items. Recent studies have assessed the psychometric properties and factor structure of the IDELA, as well as the measurement invariance of the factors across five countries(Halpin et al, 2019).Early literacy consisted of 38 items grouped into six constructs: print awareness, letter knowledge, phonological awareness, oral comprehension, emergent writing, and expressive vocabulary.An example subtask on phonological awareness asked children to identify words that begin with the same sound (e.g. 'Here is my friend mouse.…”
mentioning
confidence: 99%